Virtues in action are related to the integration of both temperament and character : comparing the VIA classification of virtues and Cloninger’s biopsychosocial model of personality - Moreira, Paulo (2022)
Evidence supports three principal virtues of Self-Control, Caring, and Inquisitiveness that represent socially-construed notions of desirable behaviors. In Study 1 (n = 509 adults), we demonstrate that the three-virtue structure identified in the VIA-IS also emerges in the VIA-72. In Study 2 (n = 659 adults) we examine the relationship between virtues and personality using correlations and person-centered analyses. Cloninger’s character dimensions, which capture the sociocognitive component of personality – Self-Directedness, Cooperativeness, Self-Transcendence – showed moderate overlap with the three virtues, but remained distinct in its silent and subjective transpersonal aspects that were excluded from VIA. People with positive development of all three character traits were the most virtuous. The specific virtues of a person depended on integrated profiles of both temperament and character. We conclude that virtues are expressed when habits are persistently regulated by all three character traits to the extent that they express selftranscendent goals and values.